1994
DOI: 10.1111/j.1365-2109.1994.tb00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimum feeding rate, and energy and protein maintenance requirements of young Clarias batrachus (L.), a cultivable catfish species

Abstract: Protein and energy maintenance and optimum feed requirements are reported in the catfisb, Clarias batrachus (L.), fed a purified diet (40% CP; 1487-lkJ/lOOg) at 0 to 8% (BW/day) ration levels. Linear (/• = 0-985) increase was observed in daily average growth increment up to a ration level of 4% (BW/day), corresponding to6 03g protein/(kg'"' BW/day) and 224-26 kJ encrgy/Ckg**" BW/day). Maintenance requirements, obtained by regressing daily average growth increment to zero, were 0-942 g/(kg''*' BW/day) for prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
5
14
1
Order By: Relevance
“…The lack of any significant effect of ration level on body composition beyond the optimum level (7%) in our study is consistent with observations reported for rainbow trout, O. mykiss (Huisman 1976), channel catfish, Ictalurus punctatus (Gatlin et al 1986) and walking catfish, C. batrachus (Hassan and Jafri 1994). The low protein retention value obtained at sub-optimal levels indicates that a substantial amount of the reduced energy intake was used to compensate the maintenance requirement at the expense of somatic growth.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The lack of any significant effect of ration level on body composition beyond the optimum level (7%) in our study is consistent with observations reported for rainbow trout, O. mykiss (Huisman 1976), channel catfish, Ictalurus punctatus (Gatlin et al 1986) and walking catfish, C. batrachus (Hassan and Jafri 1994). The low protein retention value obtained at sub-optimal levels indicates that a substantial amount of the reduced energy intake was used to compensate the maintenance requirement at the expense of somatic growth.…”
Section: Discussionsupporting
confidence: 94%
“…Increased food wastage with increasing ration has also been reported for tambaqui, Colossoma macropomum ( Van der Meer et al 1997), milkfish, Chanos chanos (Sumagaysay 1998), bagrid catfish, M. nemurus (Ng et al 2000), Chinese long snout catfish, Leiocassis longirostraris (Han et al 2004) and juvenile grass carp, Ctenopharyngodon idella (Du et al 2006). No increase in growth is achieved when the feeding rate exceeds the optimum level (Hassan and Jafri 1994;Khan et al 2004), an observation which was also noted in our study: we found an insignificant gain in weight at the super optimum ration level. An increase in ration level from 3 to 7% BW day -1 significantly (P \ 0.05) affected body composition in our study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…At lower ration level, a slightly lower fat value was observed, though at the same time the fish could manage to maintain relatively higher and constant amount of protein in their body tissue over the initial value, suggesting that in this fish, body fat is preferred as energy source over protein. Similar results on body fat were also reported in white sturgeon, Acipenser transmontanus by Hung and Lutes (1987); Brown et al (1990); Hassan and Jafri (1994); Khan et al (2004); Ahmed (2007b). Ash content of fish fed different ration levels remained insignificantly low with the increase of Fish Physiol Biochem (2010) 36:1133-11431139 Opuszynski and Shireman (1991) rations excepting at 1 and 2% ration where maximum ash content was noted.…”
Section: Discussionsupporting
confidence: 89%
“…Hassan and Jafri (1994) reported gradual decline in conversion efficiency in fish fed at higher ration levels in Clarias batrachus. Ahmed (2007b) also reported similar result in Indian major carp, Labeo rohita.…”
Section: Discussionmentioning
confidence: 95%